2012
DOI: 10.4141/cjps2012-025
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-resistant giant ragweed (Ambrosia trifida L.) control with preplant herbicides in soybean [Glycine max (L.) Merr.]

Abstract: Vink, J. P., Soltani, N., Robinson, D. E., Tardif, F. J., Lawton, M. B. and Sikkema, P. H. 2012. Glyphosate-resistant giant ragweed ( Ambrosia trifida L.) control with preplant herbicides in soybean [ Glycine max (L.) Merr.]. Can. J. Plant Sci. 92: 913–922. Giant ragweed populations in southwestern Ontario have evolved resistance to glyphosate. Glyphosate-resistant (GR) giant ragweed interference in field crops can lead to significant yield losses. Eleven field trials [five with preplant (PP) burndown only and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
33
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 28 publications
9
33
2
Order By: Relevance
“…ha -1 was needed to achieve 95% control, respectively. This is similar to the findings of Vink et al [14] who reported 97% to 98% control of glyphosate-resistant giant ragweed with glyphosate plus 2,4-D ester applied at 900 g a.e. ha -1 + 500 g a.e.…”
Section: 4-d Dose Responsesupporting
confidence: 82%
“…ha -1 was needed to achieve 95% control, respectively. This is similar to the findings of Vink et al [14] who reported 97% to 98% control of glyphosate-resistant giant ragweed with glyphosate plus 2,4-D ester applied at 900 g a.e. ha -1 + 500 g a.e.…”
Section: 4-d Dose Responsesupporting
confidence: 82%
“…In other studies, poor GR giant ragweed control with glyphosate plus flumetsulam, applied PP, has been reported ranging from 12% to 66% [13] and 26% to 61% [14], 8 WAA. Reference [17] similarly reported unacceptable giant ragweed control of 9 to 52% 8 WAA with atrazine applied PP in corn.…”
Section: Preplant Tank-mixesmentioning
confidence: 99%
“…In other PP linuron studies, Reference [24] demonstrated greater than 95% control of GR giant ragweed, while Reference [25] reported good, yet variable, control ranging from 23% to 99% at 8 WAA, in southwestern Ontario. This discrepancy in control may be due to application timing as Reference [24] applied PP linuron from May 20 to June 3, and Reference [25] during May 1 to June 2. In this study, linuron was applied May 1 to 17 ( Table 2), therefore the comparative low GR giant ragweed control may be due, in part, to early application dates.…”
Section: Resultsmentioning
confidence: 99%
“…In southwestern Ontario, giant ragweed seedlings are among the first weeds to emerge. Recent studies on GR giant ragweed have concluded that control prior to soybean planting is an effective management tactic [24] [25]. The objective of this study was to therefore determine the biologically effective dose of linuron for the control GR giant ragweed when applied pre-plant (PP) in soybean.…”
Section: Introductionmentioning
confidence: 99%